PENGARUH KEPUASAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PERTANAHAN NASIONAL KOTA MAKASSAR - Ahmad Syarifuddin; Burhanuddin; Uhud Darmawan Natsir; Romansyah Sahabuddin; Zainal Ruma (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to (1) determine the effect of satisfaction on employee performance, (2) determine the effect of work discipline on employee performance, (3) determine the effect of satisfaction and work discipline jointly on employee performance at the National Land Agency in Makassar City . The data used in this study are primary and secondary data with a total sample of 63 respondents. This study used a quantitative approach and was analyzed using multiple linear regression analysis with the help of SPSS 25 data processing to prove three hypotheses. The results of this study prove that the satisfaction variable has a significant effect on employee performance, t count > t table where 3.434 > from t table of 1.671. The work discipline variable has a significant effect on employee performance because the value of t count > t table is where 5.056 > from T table of 1.671. Based on the results of this study it is also known that the independent variables jointly or simultaneously have a significant effect on the dependent variable, namely the performance of employees at the Makassar City National Land Agency. Therefore, if Satisfaction and Work Discipline are continuously improved, then of course performance will be more optimal.